Primary Education and Healthcare Service Delivery by Local Government in Oyo State, Nigeria - Adelabu, Salihu Abdul Wahed (2010)
The main purpose of creating local governments in Nigeria is to deliver social and welfare services to the people in the local area. This research study is interested in primary education and healthcare service delivery by local governments in Oyo state of Nigeria. There are a lot of hindrances militating against the delivery of these services to the people at the grassroots. amongst which are insufficient funds, corruption, leadership quality, bad governance, managerial accountability, leadership problem, instability in governance, and government policy from other tiers of government. Out of these multifarious problems, this research study focuses on three main factors, namely statutory allocation/fund, managerial accountability, and leadership structure in the local governments. The study wants to evaluate the relationship between service delivery (primary education and healthcare service) and these variables. These variables are treated as independent variables, while service delivery is treated as the dependent variable. Multiple regression analysis is used to predict the unique significant contribution of the three variables to the delivery of primary education and healthcare service by local governments in Oyo state. The findings of the study show that there exist positive relationship between service delivery and the three variables. The correlation coefficient between statutory allocation/fund and service delivery is given as 0.643, while the correlation coefficient between managerial accountability and service delivery is given as 0.254. And the correlation coefficient between leadership structure and service delivery is given as 0.457. Multiple Regression analysis shows that the variables are correlated, and have unique significant role to the delivery of primary education and healthcare service by the local governments. The significant values for the variables are given as statutory allocation/fund (0.000), managerial accountability (0.040), and leadership structure (0.0 13). Similarly, statutory allocation disbursed to local governments in Oyo state for 2007, 2008 and 2009, and approved annual budget for the fiscal year 2008 of four local governments in Oyo state are analyzed to evaluate the expenditure trend for primary education and healthcare service in order to determine the rate at which primary education and healthcare service is delivered. It is established by the study that < 5% of the statutory allocation is being utilized for primary education and healthcare service, while > 10% is being utilized for personnel expenditure as the cost of delivering primary education and healthcare service. This shows that local governments in Oyo state are not delivering optimum primary education and healthcare service to the people in the local area. It is therefore recommended that there is need for proactive measure to improve upon the delivery of primary education and healthcare service by local governments in Oyo state of Nigeria.